C-terminal citrullinated peptide alters antigen-specific APC:T cell interactions leading to breach of immune tolerance. Issue 135 (February 2023) - Malcolm, J.; Nyirenda, M.H.; Brown, J.L.; Adrados-Planell, A.; Campbell, L.; Butcher, J.P.; Glass, D.G.; Piela, K.; Goodyear, C.S.; Wright, A.J.; McInnes, I.B.; Millington, O.R.; et al.
Abstract: In rheumatoid arthritis, the emergence of anti-citrullinated autoimmunity is associated with HLA-antigen-T cell receptor complexes. The precise mechanisms underpinning this breach of tolerance are not well understood. Porphyromonas gingivalis expresses an enzyme capable of non-endogenous C-terminal citrullination with potential to generate citrullinated autoantigens. Here we document how C-terminal citrullination of ovalbumin peptide 323-339 alters the interaction between antigen-presenting cells and OTII T cells to induce functional changes in responding T cells. These data reveal that C-terminal citrullination is sufficient to breach T cell peripheral tolerance in vivo and reveal the potential of C-terminal citrullination to lower the threshold for T cell activation. Finally, we demonstrate a role for the IL-2/STAT5/CD25 signalling axis in breach of tolerance. Together, our data identify a tractable mechanism and targetable pathways underpinning breach of tolerance in rheumatoid arthritis and provide new conceptual insight into the origins of anti-citrullinated autoimmunity. Graphical abstract: Image 1 Highlights: Antigen-specific OTII T cells respond to C-terminal citrullinated peptide antigen. OTII T cells respond to citrullinated peptide with enhanced effector function. C-terminal citrullination is sufficient to breach T cell peripheral tolerance. C-terminal citrullination lowers the threshold for T cell activation. The IL-2/STAT5/CD25 axis is implicated in breach of tolerance to citrullinated antigen.